Leaf Epiphytic Bacteria of Plants Colonizing Mine Residues: Possible Exploitation for Remediation of Air Pollutants - Sánchez-López, Ariadna S.; González-Chávez, Ma. del Carmen A.; Solís-Domínguez, Fernando A.; Carrillo-González, Rogelio; Rosas-Saito, Greta H. (Frontiers in Microbiology, 2018)
Plant surfaces are known as an important sink for various air pollutants, including particulate matter and its associated potentially toxic elements (PTE). Moreover, leave surface or phylloplane is a habitat that harbors diverse bacterial communities (epiphytic). However, little is known about their possible functions during phytoremediation of air pollutants like PTE. The study of leaf epiphytic bacteria of plants colonizing mine residues containing PTE is thus a key to understand and exploit plant-epiphytic bacteria interactions for air phytoremediation purposes. In this research, we aimed (i) to characterize the functions of epiphytic bacteria isolated from the phylloplane of Brickellia veronicifolia, Flaveria trinervia, Gnaphalium sp. and Allionia choisyi growing spontaneously on multi-PTE contaminated mine residues (MR) and (ii) to compare these against the same plant species in a non-polluted control site (NC). Concentrations (mg kg-1) of PTE on MR leaf surfaces of A. choisyi reached up to 232 for Pb, 13 for Cd, 2728 for As, 52 for Sb, 123 for Cu in F. trinervia and 269 for Zn in Gnaphalium sp. In the four plant species, the amount of colony-forming units per cm-2 was superior in MR leaves than in NC ones, being A. choisyi the plant species with the highest value. Moreover, the proportion of isolates tolerant to PTE (Zn, Cu, Cd and Sb), UV light and drought was higher in MR leaves than in those in NC. Strain BA15, isolated from MR B. veronicifolia, tolerated 150 mg Zn L-1, 30 mg Sb L-1, 25 mg Cu L-1; 80 mg Pb L-1, and was able to grow after 12 h of continuous exposition to UV light and eight weeks of drought. Plant growth promotion related traits (N fixation, indol acetic acid production, phosphate solubilization) of bacterial isolates varied among plant species isolates and between MR and NC sampling condition. The studied epiphytic isolates possess functions interesting for phytoremediation of air pollutants. The results of this research may contribute to the development of novel and more efficient inoculants for microbe-assisted phytoremediation applied to improve air quality in areas exposed to the dispersion of metal mine tailings.